2011
DOI: 10.1002/hbm.21427
|View full text |Cite
|
Sign up to set email alerts
|

Acquired self‐control of insula cortex modulates emotion recognition and brain network connectivity in schizophrenia

Abstract: Real-time functional magnetic resonance imaging (rtfMRI) is a novel technique that has allowed subjects to achieve self-regulation of circumscribed brain regions. Despite its anticipated therapeutic benefits, there is no report on successful application of this technique in psychiatric populations. The objectives of the present study were to train schizophrenia patients to achieve volitional control of bilateral anterior insula cortex on multiple days, and to explore the effect of learned self-regulation on fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
241
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(254 citation statements)
references
References 89 publications
9
241
1
Order By: Relevance
“…The results showed that participants who initially trained via the AS interface were better able to regulate the amyg-EFP in the absence of online feedback (open-loop Brain-Computer Interface), indicating better learning sustainability ( Figure 4A). This "sustainability effect" in a no-feedback trial was demonstrated in previous studies, although mostly conducted immediately after one NF session (i.e., at the same day) (deCharms et al, 2004(deCharms et al, , 2005Ruiz et al, 2013;Sulzer et al, 2013a,b). In the current study, we further challenged our trainees by conducting the no-feedback trial 1 week following the initial NF session, with no refresher training in between.…”
Section: Discussionsupporting
confidence: 65%
“…The results showed that participants who initially trained via the AS interface were better able to regulate the amyg-EFP in the absence of online feedback (open-loop Brain-Computer Interface), indicating better learning sustainability ( Figure 4A). This "sustainability effect" in a no-feedback trial was demonstrated in previous studies, although mostly conducted immediately after one NF session (i.e., at the same day) (deCharms et al, 2004(deCharms et al, , 2005Ruiz et al, 2013;Sulzer et al, 2013a,b). In the current study, we further challenged our trainees by conducting the no-feedback trial 1 week following the initial NF session, with no refresher training in between.…”
Section: Discussionsupporting
confidence: 65%
“…This study demonstrates that neurofeedback is able not only to alter connectivity between two functionally distinct brain networks but also to exert long-term effects. Network reorganization resulting from neurofeedback training of single regions was observed in earlier studies 34,35 , whereas recent studies have attempted neurofeedback training of functional connectivity between brain regions. For example, in one study, participants were trained to be able to alter the level of interhemispheric motor cortical coherence through the use of contingent magnetoencephalography-based neurofeedback, leading to proportional changes in asynchronous finger tapping 36,37 .…”
Section: Coherencementioning
confidence: 92%
“…As it turns out, few studies examine sustainability in neurofeedback (Thibault et al, 2015). Whereas some experiments demonstrate that participants retain control over target brain regions Mathiak et al, 2015;Robineau et al, 2014;Scharnowski et al, 2015;Zotev, Phillips, Young, et al, 2013;Zotev, Phillips, Yuan, et al, 2013;Zotev et al, 2011), other studies report no such retention (Berman, Horovitz, & Hallett, 2013;Greer et al, 2014;Hamilton et al, 2011;Ruiz et al, 2013;. Thus, the conundrums of mental strategy and sustainability still beg resolution.…”
Section: Fmrimentioning
confidence: 99%
“…According to some studies, modulating activity in the insula appears to influence the perceived valence of emotional stimuli (Caria et al, 2010;Ruiz et al, 2013); yet one of these studies had no control group and another experiment suggested that control over activity in the insula area hardly related to valence ratings (Lawrence et al, 2014).…”
Section: Fmrimentioning
confidence: 99%
See 1 more Smart Citation